Bioclimatic Solutions in the 1950s: A Study of the Cristal Racecourse and the Esplanada Building - Rodrigues, Larissa; Souto, Ana Elisa (National Journal of City Management, 2025)
Objective – To analyze the bioclimatic strategies applied in two Modern Architecture works in Porto Alegre, RS: the Cristal Racecourse (1951–1959) and the Esplanada Building (1952–1962), both designed by Uruguayan architect Román Fresnedo Siri.Methodology – The study adopts the tools provided by the ProjetEEE platform and the criteria of the Casa Azul Seal from Caixa, evaluating aspects such as site planning, natural ventilation and lighting, functionality, and materiality.Originality/Relevance – The research addresses a theoretical gap in the field of South American modern architecture by investigating how bioclimatic principles were integrated into prominent 1950s designs.Results – The findings show that both projects present functional and technological solutions that were innovative for their time, reflecting a conscious response to climate and urban context.Theoretical/Methodological Contributions – The study emphasizes the relevance of bioclimatic analysis tools in researching modern architectural heritage, bridging historical design practices with contemporary sustainability criteria.Social and Environmental Contributions – The analyses highlight the early incorporation of sustainable and context-sensitive strategies, contributing to the current discourse on energy efficiency and environmental comfort.
Keywords: Cristal Racecourse; Esplanada Building; Bioclimatic Analysis